Effects of nonoxynol-9 (N-9) on sperm functions: systematic review and meta-analysis - Murong Xu; Mingpeng Zhao; Raymond Hang Wun Li; Zhixiu Lin; Jacqueline Pui Wah Chung; Tin Chiu Li; Tin-Lap Lee; David Yiu Leung Chan (Bioscientifica, 2022)
Objective: To summarize the currently available phase I and II clinical trials of the effects of nonoxynol-9 (N-9) on human sperm structure and functions. Methods: A systematic review and meta-analysis aiming to evaluate the spermicidal activity of N-9 on motility, was conducted in PubMed, EMBASE, and Cochrane databases by 10 March 2021. The counted numbers of progressive motile (PR) sperm in cervical mucus and the vanguard sperm penetration distances were analyzed. Other effects on sperm structures and physiological activities were reviewed as well. Results: In the pooled results, percentages or counted numbers of PR sperm decreased after the treatment of N-9. Vanguard sperm penetration distance was shortened in treated groups. N-9 has been confirmed to damage the structures of sperm, as well as other organelles like acrosome and mitochondria. The physiological activities such as generation of reactive oxygen species, superoxide dismutase activity, acrosin activity, and hemizona binding were all inhibited in the reviewed studies. Conclusions: N-9 has several impacts on sperm owing to its potency in reducing sperm motility and cervical mucus penetration, as well as other functional competencies.